Factors associated with achieving target serum uric acid level and occurrence of gouty arthritis: A retrospective observational study of Japanese health insurance claims data. Issue 2 (16th September 2020) - Koto, Ruriko; Nakajima, Akihiro; Horiuchi, Hideki; Yamanaka, Hisashi
Abstract: Purpose: This study assessed factors associated with achieving target serum uric acid (sUA) level and occurrence of gouty arthritis in Japanese clinical practice. Methods: Japanese health insurance claims and medical check‐up data from October 2015 to March 2017 were analyzed to assess factors associated with target sUA achievement in gout and asymptomatic hyperuricemia and gouty arthritis in gout. Target sUA was further assessed by subgroup analysis of urate‐lowering therapy (ULT) prescriptions and outcomes, stratified by renal function. Results: Patients achieving target sUA tended toward older, female, higher ULT dose, higher adherence, more comorbidities, and/or antidiabetic drugs prescribed. Renal dysfunction and/or diuretic prescriptions were associated with reduced achievement of target sUA. Severe renal dysfunction was particularly influential (odds ratio [OR] = 0.22 [95% confidence interval (CI): 0.10‐0.48] for <15, 0.15 [0.10‐0.23] for ≥15 to <30, compared with eGFR ≥90 mL/min/1.73 m 2 ). Across all renal function categories, mean prescribed ULT dose was low (febuxostat 17.0‐21.0 mg/day, allopurinol 123.1‐139.6 mg/day), and target sUA achievement was reduced among renal dysfunction patients. Gouty arthritis was more likely in patients with a prior history of such occurrences, and less likely for higher ULT adherence, sUA monitored regularly at medical facilities, and/or more comorbidities. Conclusion: In a real‐world setting, severe renal dysfunction is the most important risk factor for failure to achieve the target sUA, suggesting suboptimal disease management in patients with gout or hyperuricemia complicated by this condition. Findings associated with gouty arthritis suggest that these occurrences could be successfully managed by regular monitoring of sUA and closer adherence to ULT.